(3GdeGdjI GdYGeI (B/s - (3Ndjd, Ydjs; (3GddhRj, SdjeGf s ((3YeGf(B: s (3OGQ RgQGJ(B, s, 2000)
(3ebOeI YGeI Mhd Yde GdeGdjI h GdfTGW GdeGdj , hXGFa GdeGdjI GdYGeI , GdfabGJ h bhGYOgG h gjGcdgG , GdfabGJ h JRGjOgG , JCKjQ GdfabGJ GdYGeI , GdGjQGOGJ GdeMdjI ZjQ GdVQjHjI h GdGjQGOGJ GdeMdjI GdVQjHjI , GdJfXje Gdafj ddVQjHI , Gdgjcd GdVQjHj h GdYHA GdVQjHj , GdbQhV h GdGYGfGJ , GgOGa GdehGRfI h eQGMdgG h GdbhGYO GdJj JMcegG , JWHjbGJ Mhd eTcdGJ GdehGRfI aj GdOhd GdfGejI h GdehGRfI GdYGeI aj GdOhd GdfGejI (B( (3OQGSI JWHjbjI (B).s
(3eQGLY U(B.393 (3;GdghGeT U(B.391s
Keywords: (3GdeGdjI GdYGeIs